Degree, but not direction of grip strength asymmetries, is related to depression and anxiety in an elderly population. Issue 3 (4th May 2017) - Yu, Junhong; Rawtaer, Iris; Mahendran, Rathi; Kua, Ee-Heok; Feng, Lei
ABSTRACT: Despite the abundance of studies on asymmetries in manual laterality, a marker for atypical brain lateralization in depression and anxiety, findings in this area are mixed. Traditionally, research have looked at individual differences in depression and anxiety as a function of the direction of asymmetry. However, recent research has emphasized on studying the degree of asymmetry in addition to its direction. To these ends, the present study aims to unravel the associations between the degree and direction of manual lateralization, and depression/anxiety. Cognitively healthy elderlies ( N = 326, 91 males, M age = 68) were administered grip strength assessments on both hands and self-report measures of depression and anxiety. Partial correlation analyses controlling for age, education and sex revealed significant positive associations between degree of lateralization and anxiety in the overall sample and among right-dominant participants, as well as a significant positive relationship between degree of lateralization and depression among right-dominant participants. None of the correlations involving the direction of lateralization yielded significance, neither was there significant differences between left- and right-dominant participants on depression and anxiety scores. These findings suggest that the degree of manual lateralization, but not direction, is related to depression and anxiety at least among right-dominant individuals.